Evaluation of Tall Fescue Cultivars - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2017)
Spring 2016 yield of tall fescue was higher for ‘NFTF 1051’ than for 12 of the 19 other cultivar entries. Summer production of ‘PBU-B2’ was greater than summer production of the three lower-yielding entries. Fall production of ‘BarOptima PLUS E34’ was higher than that of 12 other cultivar entries, but total 2016 production was greater for PBU-B2, ‘PBU-B7’, and NFTF 1051 than for eight other cultivars.
Keywords: endophyte-free; non-toxic fescue; endophyte-infected